2001
DOI: 10.1159/000054643
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid and Mineralocorticoid Receptors Are Involved in the Facilitation of Anxiety-Like Response Induced by Restraint

Abstract: In previous studies, we have shown that male Wistar rats exposed to a single inescapable stressor session (15 min restraint) exhibited 24 h later an anxiogenic-like behavior in the elevated plus-maze (EPM), which was reversed by inhibition of corticosterone (CS) synthesis with metyrapone (75 mg/kg i.p.) 3 h before stress. Since CS binds to two central corticosteroid receptors, the mineralocorticoid (MR) and the glucocorticoid (GR) receptors, involvement of MR and GR in the modulation of anxiogenic responses wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 48 publications
5
55
0
Order By: Relevance
“…These behavioral changes that occur during exposure to stress seem to reflect a decrease in anxiety. Other studies show that administration of metyrapone 3 h before exposure to restraint stress increases the spent time in the open arms during testing in an ETM [44,76]. Moreover, it has been shown that after administration of metyrapone, there are increases in the levels of 11-deoxycortisol and deoxycorticosterone [48], both of which are precursors for the synthesis of corticosterone.…”
Section: Discussionmentioning
confidence: 99%
“…These behavioral changes that occur during exposure to stress seem to reflect a decrease in anxiety. Other studies show that administration of metyrapone 3 h before exposure to restraint stress increases the spent time in the open arms during testing in an ETM [44,76]. Moreover, it has been shown that after administration of metyrapone, there are increases in the levels of 11-deoxycortisol and deoxycorticosterone [48], both of which are precursors for the synthesis of corticosterone.…”
Section: Discussionmentioning
confidence: 99%
“…The final concentration of ethanol was less than 1%. 22 Rats were gently held in a soft cotton towel every day for 2 weeks before the injection. On the injection day, IL-1b, RU486 or saline were taken into an injection needle (4.2 mm length) that was connected to a PE 50 polyethylene tube.…”
Section: Reagents and Icv Injection Proceduresmentioning
confidence: 99%
“…Adrenal steroids play an important role in regulating both learned and unlearned fear and anxiety (Korte 2001;Calvo et al, 1998;Calvo and Volosin, 2001) and alterations in the balance between Type I or mineralocorticoid receptors (MR) and Type II or glucocorticoid receptors (GR) in the brain appear to play a role in these behaviors as well as in the etiology of depression and anxiety (de Kloet et al, 1988;Korte, 2001). MR and GR are expressed throughout the central nervous system, with GR showing a more widespread distribution and MR showing a discrete localization, such as in neurons of the hippocampus, regions of the amygdala, and brain stem (Ahima and Harlan, 1990;Ahima et al, 1991).…”
Section: Introductionmentioning
confidence: 99%